2020
DOI: 10.1049/iet-rpg.2019.0663
|View full text |Cite
|
Sign up to set email alerts
|

Increasing operational flexibility of integrated energy systems by introducing power to hydrogen

Abstract: Owing to the limited operating regions of combined heat and power (CHP) units, the operation of integrated energy systems suffers from low flexibility, low-cost efficiency, renewable curtailment etc. Meanwhile, as the capacity of renewable energies keeps growing and integrating into power systems, various methods, such as installing electric boilers to enable electricity-heat conversion, have been developed to absorb excessive renewables and increase system operation flexibility. To further increase the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The uncertainty of renewables raises natural concerns of maintaining the real-time balance between energy demand and supply, along with reducing the curtailment of renewables. As integrated energy systems (IESs) include various devices and couples heating and electricity systems, they can help improve the operating flexibility of energy systems [2,3]. Thus, developing IES has been considered a feasible pathway to reliable and economic renewable-powered energy systems [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainty of renewables raises natural concerns of maintaining the real-time balance between energy demand and supply, along with reducing the curtailment of renewables. As integrated energy systems (IESs) include various devices and couples heating and electricity systems, they can help improve the operating flexibility of energy systems [2,3]. Thus, developing IES has been considered a feasible pathway to reliable and economic renewable-powered energy systems [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the power-to-hydrogen (P2H) is recognised as a promising method to enhance the economics of IES further, and help reduces renewable curtailments [3]. Because hydrogen can generate heat and electricity, produce methane, and power fuel cell vehicles [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELZs have the potential to participate in the provision of primary service [4] and perform faster in frequency support than conventional generators [5]. In [6], it is shown that utilising ELZs can increase the operational flexibility of an integrated energy system consisting of combined heat and power and wind power. Also, a set of an ELZ and FC can be integrated into a stand-alone microhydro plant or a microgrid to provide long-term energy balance [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The produced hydrogen or hydrocarbons can be stored in gas storage tanks or injected into the natural gas network, for which the surplus RDG can be spatially or temporally shifted [34,35]. Due to the compressibility of gas, more flexibility can be exploited to improve operational efficiency [36]. In the inner processes of P2G stations, it is the first step that the alternating current is converted to the direct current which is used for electrolysis.…”
Section: Introductionmentioning
confidence: 99%